1969
DOI: 10.1002/cjce.5450470308
|View full text |Cite
|
Sign up to set email alerts
|

Solids concentration profile in the bubble column slurry reactor

Abstract: Solids concentration profile was measured for the basic babble column slurry reactor configuration: steady flow with respect to gas and batch with respect to solid and liquid. The result confirmed the exponential profile predicted by a diffusion model. An application is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(1966), Imafuku et al (1968), Farkas and Leblond (1969), and Narayanan et al (1969). Cova (1966) studied the effects of liquid velocity, gas velocity, and liquid viscosity on the solid concentration profile and concluded that higher gas and liquid velocities and high viscosities all tend to give more uniform solid distributions.…”
Section: Resultsmentioning
confidence: 99%
“…(1966), Imafuku et al (1968), Farkas and Leblond (1969), and Narayanan et al (1969). Cova (1966) studied the effects of liquid velocity, gas velocity, and liquid viscosity on the solid concentration profile and concluded that higher gas and liquid velocities and high viscosities all tend to give more uniform solid distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Cova (1966) measured the steady state concentration distribution of solids in a three-phase reactor. Farkas and Leblond ( 1969) used such data to calculate the backmixing coefficient of solids.…”
Section: Ezlaul'"' (491mentioning
confidence: 99%
“…It is recognized that a three-phase fluidized bed is rather difficult to design because the phase holdups are axially distributed in the column. Many works (Cova, 1966;Imafuku et al, 1968; Farkas and Leblond, 1969;Kato et al, 1985; Smith and Ruether, 1985;Smith et al, 1986; Morooka et al, 1986; Murray and Fan, 1989) have been published, especially on the behavior of solid particles in three-phase fluidization, but most were restricted to the case of particles with the same size and density. When a mixture of solid particles is used as the solid phase, on the other hand, segregation of components naturally occurs in the bed.…”
Section: Introductionmentioning
confidence: 99%